Role of microRNA carried by small extracellular vesicles in urological tumors - Mao, Yiping; Zhang, Mengting; Wang, Lanfeng; Lu, Yukang; Hu, Xinyi; Chen, Zhiping (Frontiers in Cell and Developmental Biology, 2023)
Small extracellular vesicles (sEVs) are minute vesicles secreted by various cells that are capable of transporting cargo, including microRNAs, between donor and recipient cells. MicroRNAs (miRNAs), small non-coding RNAs approximately 22 nucleotides in length, have been implicated in a wide array of biological processes, including those involved in tumorigenesis. Emerging evidence highlights the pivotal role of miRNAs encapsulated in sEVs in both the diagnosis and treatment of urological tumors, with potential implications in epithelial-mesenchymal transition, proliferation, metastasis, angiogenesis, tumor microenvironment and drug resistance. This review provides a brief overview of the biogenesis and functional mechanisms of sEVs and miRNAs, followed by a summarization of recent empirical findings on miRNAs encapsulated in sEVs from three archetypal urologic malignancies: prostate cancer, clear cell renal cell carcinoma, and bladder cancer. We conclude by underscoring the potential of sEV-enclosed miRNAs as both biomarkers and therapeutic targets, with a particular focus on their detection and analysis in biological fluids such as urine, plasma, and serum.